Heroes, Tricksters, Monsters, and Caretakers: Indigenous Law and Legal Education - Borrows, John (McGill Law Journal / Revue de droit de McGill, 2016)
Teaching Indigenous peoples’ own law in Canadian law schools presents significant challenges and opportunities. Materials can be organized in conventional or innovative ways. This article explores how law professors and others might best teach Indigenous peoples’ law. Questions canvassed include: whether Indigenous peoples’ law should primarily be taught in Indigenous communities, whether such law should even be taught in law schools, whether it is possible to categorize Indigenous peoples’ law or teach it in English, and whether it is possible to theorize Indigenous peoples’ law within a single framework or organize the subject within common law categories. While this article suggests that Indigenous peoples’ law can be discussed in numerous ways, including within conventional law school frameworks, it emphasizes that such law is best taught in other ways. Indigenous legal traditions should be organized in accordance with Indigenous frameworks. Some of these frameworks include Heroes, Tricksters, Monsters, and Caretakers. Using these Anishinaabe law examples, this article stresses how the teaching of Indigenous peoples’ law should be done in culturally appropriate ways that open rather than confine fields of inquiry within Indigenous law and practice.